Survey of Small Mammals in Bukit Taat, Tasik Kenyir, Hulu Terengganu, Malaysia. - Mazlan, Norfarhana; Tan, Chin-Fang; Kamaruzzaman, Mohamad Abid; Adrus, Madinah; Abdullah, M.T. (Borneo Journal of Resource Science and Technology, 2016)
A survey on small mammals was conducted at Bukit Taat, Tasik Kenyir from 2nd to 5th September 2014. This survey aimed to document the species diversity of small mammals in Bukit Taat. A total of eight mist nets, two four-bank harp traps and 50 cage traps baited with banana slices were used. A total of 36 individuals comprising 14 species of chiropteran but none of non-volant small mammals were recorded. Hipposideros larvatus (36.1% of total individuals) were recorded as the most captured species followed by H. diadema (19.4% of total individuals) and Penthetor lucasi (8.3% of total individuals). This survey formed the first list of chiropterans recorded at Bukit Taat, Tasik Kenyir, Hulu Terengganu, Malaysia.